2018
DOI: 10.1016/j.jneuroim.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors 4, 5, 6 and 7 are constitutively expressed in non-human primate retinal neurons

Abstract: The purpose of this study was to characterize cell-specific expression patterns of Toll-like receptors (TLR) in non-human primate (NHP) neural retina tissue. TLR 4, 5, 6, and 7 proteins were detected by immunblotting of macaque retina tissue lysates and quantitative PCR (qPCR) demonstrated TLRs 4-7 mRNA expression. Immunofluorescence (IF) microscopy detected TLRs 4-7 in multiple cell types in macaque neural retina including Muller, retinal ganglion cells (RGC), amacrine, and bipolar cells. These results demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…In the CNS, TLR2 and TLR4 are primarily expressed on astrocytes and microglia ( 29 , 38 ), but are also present on neurons ( 38 , 39 ) and CNS infiltrating T cells ( 40 , 41 ). Toll-like receptor 2 and 4 are activated by DAMPs from breakdown of myelin and other damaged and inflamed cells, including products such as heat shock protein 60 (HSP60), HSP70, high mobility group box 1 (HMGB1), alpha-synuclein, hyaluronic acid, fibrinogen, and biglycan ( 61 , 73 , 80 86 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CNS, TLR2 and TLR4 are primarily expressed on astrocytes and microglia ( 29 , 38 ), but are also present on neurons ( 38 , 39 ) and CNS infiltrating T cells ( 40 , 41 ). Toll-like receptor 2 and 4 are activated by DAMPs from breakdown of myelin and other damaged and inflamed cells, including products such as heat shock protein 60 (HSP60), HSP70, high mobility group box 1 (HMGB1), alpha-synuclein, hyaluronic acid, fibrinogen, and biglycan ( 61 , 73 , 80 86 ).…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptors 2 and 4 antagonists are one promising strategy to treat pain from MS ( 16 ), as well as neuropathic pain from both peripheral and central origin ( 34 37 ). Toll-like receptors 2 and 4 are commonly expressed on glial cells ( 29 , 38 ) as well as less commonly on neurons ( 38 , 39 ) and T cells ( 40 , 41 ). Importantly, TLR2–TLR4s are upregulated in white matter of patients with MS ( 42 44 ) as well as in EAE ( 42 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, studies have demonstrated that mammalian TLRs and their Drosophila homologs trigger cell-autonomous processes independent of ligand activation during embryogenesis [ 3 ] and adult neurogenesis [ 6 8 ]. Constitutive expression of several TLR family members occurs in astrocytes [ 9 ], oligodendrocytes [ 10 ], neurons [ 11 , 12 ], and neural precursor cells (NPCs) [ 13 ]. Additionally, recent research has suggested a role for TLR2 and TLR4 in supporting neuronal morphogenesis and plasticity under physiological [ 3 , 7 ] and pathological conditions [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, studies have demonstrated that mammalian TLRs and their Drosophila homologs trigger cell-autonomous processes independent of ligand activation during embryogenesis [3] and adult neurogenesis [6][7][8]. Constitutive expression of several TLR family members occurs in astrocytes [9], oligodendrocytes [10], neurons [11,12], and neural precursor cells (NPCs) [13]. Additionally, recent research has suggested a role for TLR2 and TLR4 in supporting neuronal morphogenesis and plasticity under physiological [3,7] and pathological conditions [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%